Wpływ warunków siedliskowych na rozwój korzeni jesionu w wierzchnich warstwach gleby - Farfał, Dorota (Leśne Prace Badawcze, 2011)
The density of European ash ( Fraxinus excelsior L.) roots (g/100 cm -3 of soil) in two topsoil layers (layer 1: 0–5 cm, and layer 2: 5–15 cm) was compared in two habitats. The study was conducted in ash stands aged between 38–43 years old, representing the most typical of European ash forest habitat types: alder-ash (OlJ) and moist deciduous forest (Lw). The root system of ash was more extensive when growing in the ash-alder forest (soil layer 1: 0.635 g/100 cm 3 of soil, and soil layer 2: 0.682 g /100 cm 3 of soil) than in the moist deciduous forest (soil layer 1: 0.374 g /100 cm 3 of soil, soil layer 2: 0.229 g / 100 cm 3 of soil). There was an increase in the proportion of fine roots (20 mm diameter) going from ash-alder to moist deciduous habitat. In OlJ course roots made up 75–85% of total root weight (soil layer 1: Lw – 0.143 g/100 cm 3 of soil OlJ – 0.038 g /100 cm 3 of soil, soil layer 2: Lw – 0.054 g/100 cm 3 of soil, OlJ – 0.008 g /100 cm 3 of soil). The average density of ash fine roots, was significantly higher in ash-alder forest than moist deciduous forest in both the soil layers studied. Moreover, in the upper soil layer in the ash-alder habitat, the density of dead fine roots (0.05 g /100 cm 3 of soil) was 1.3 times higher than the density of live fine roots of ash (0.038 g cm 3 of soil), while in the Lw habitat it was twofold lower than the density of fine roots (soil layer 1: 0.069 g /100 cm 3 of soil, soil layer 2: 0.143 g/100 cm 3 of soil). The ratio between the density of live fine roots of ash and the density of all species together, as well as dead fine roots may indicate a faster rate of turnover of fine roots of ash in the ash-alder habitat than moist deciduous forest, particularly during periods of adverse weather conditions (e.g. drought, spring/summer and autumn during active growth of roots).